Prevalence and characteristics of Shiga-toxin producing Escherichia coli (STEC) isolated from beef slaughterhouse - Parvej, Md. Shafiullah; Mamun, Montasir; Hassan, Jayedul; Mahmud, Md. Muket; Rahman, Marzia; Rahman, Md. Tanvir; Rahman, Md. Bahanur; Nazir, K. H. M. Nazmul Hussain (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: Shiga-toxin producing Escherichia coli (STEC) is the most important foodborne bacterial pathogen worldwide and the bovine animals are assumed as a reservoir of this pathogen. The present study was conducted to assess the role of bovine animals as the source of STEC. Materials and methods: To assess the role of bovine animals as the source of STEC, we examined 100 samples (50 rectal swab and 50 beef samples) collected from the local beef slaughterhouses by cultural, morphological, biochemical tests and polymerase chain reaction. Finally, the drug resistance pattern of isolated organisms has been examined. Result: In the preliminary screening by polymerase chain reaction (PCR), E. coli was more prevalent in rectal swab (n=21/50) than beef samples (n=16/50). Among 39 isolated E. coli, 10 isolates were confirmed as STEC (Rectal swab=7, Beef=3) by PCR, where stx2 gene (n=7/10) was predominant than stx1 gene (n=3/10). Remaining 29 isolates did not react to stx primers in PCR. Presence of STEC in beef samples was significantly associated with the fecal contamination at P≤0.1 (0.074818) in Pearson’s correlation coefficient method. In addition, most of the isolated STEC strains were resistant to one or more commonly used antimicrobials in the country. Conclusion: The bovine animals and its products could be an important source of multidrug-resistant STEC in the country. http://doi.org/10.5455/javar.2018.e271